Mangrove Community Structure in Pematang Sei Baru Village, Tanjung Balai District, Asahan Regency - Sitorus, Reaful Samuel; Barat, Welmar Olfan Basten; Handoco, Ewin (Journal of Applied Geospatial Information, 2023)
Coastal and marine areas are an integrated ecosystem and are interconnected with each other, so they have a mutual correlation. In a coastal ecosystem, there is an exchange of matter and energy that takes place in the system and with other external system components. Based on the importance of the role of mangrove ecosystems in a body of water and the lack of information about the structure of mangrove communities in Pematang Sei Baru Village, Tanjung Balai District, Asahan Regency, North Sumatra, this research is important to be carried out to determine the condition of mangrove ecosystems and can provide understanding to the community about the importance of ecosystems for coastal areas. The data analysis used in this study is both descriptive and quantitative. The data analysis used includes diversity and uniformity index, dominance, mangrove community structure, and canopy cover. The highest diversity in trees is found at station 3, with a value of 2.20, and the lowest, with a value of 2.12, at station 2. The highest uniformity in trees is found at station 2, with a value of 0.96, and the lowest at station 5, with a value of 0.93. The highest dominance value was in Rhizophora mucronata with a value of 15.75%, Xylocarpus granatum with a value of 11.51%, and Bruguiera cylindrical type with a value of 10.73%. 1 highest INP value is the type of Rhizophora mucronata with a value of 55.79% and canopy cover in the medium category. Based on the results of observations made at the location of this study, there are many remnants of logging carried out by the surrounding community, which, if left unchecked, will lead to reduced land, which will greatly affect the ecosystem in it. Therefore, the role of the government is expected in conducting supervision in this area.